THE ROLE OF ONOMASTICS IN LINGUISTICS - Erkinova Farzona; Khakimbayeva O.K. (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
Onomastics, the scientific study of names, occupies an important place in modern linguistics as it reflects the interaction between language, culture, history, and society. This article explores the role of onomastics within linguistic studies, focusing on its main branches, functions, and significance in understanding national identity and cultural heritage. Drawing on principles commonly discussed in Uzbek linguistic scholarship, the paper highlights how proper names serve not only as linguistic units but also as carriers of historical and social information. The study emphasizes the interdisciplinary nature of onomastics and its contribution to lexicology, sociolinguistics, and cultural studies.